2021
DOI: 10.1021/acsearthspacechem.1c00138
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Ice Nucleation of Simulated Sea Salt Particles with the Addition of Anthropogenic Per- and Polyfluoroalkyl Substances

Abstract: Ice-nucleating particles (INPs) impact global climate by altering cloud formation and properties. The ability of aerosol particles to nucleate ice is in part determined by particle composition. Here, we demonstrate that the addition of common fluorinated pollutants to seawater can enhance the ice nucleation activity of resulting simulated sea spray particles, although we note that ambient sea spray will have additional organic components not considered here. We quantified the ice supersaturation at the onset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 122 publications
(254 reference statements)
0
5
0
Order By: Relevance
“…45 Recent evidence even suggests that PFAS may enhance ice nucleation by aerosol particles. 46,47 However, relatively few studies have explored impacts of PFAS on cloud formation through either CCN or ice nucleating particles.…”
Section: Introductionmentioning
confidence: 99%
“…45 Recent evidence even suggests that PFAS may enhance ice nucleation by aerosol particles. 46,47 However, relatively few studies have explored impacts of PFAS on cloud formation through either CCN or ice nucleating particles.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, organic matter is a common type of aerosol found in the atmosphere, but its effect on IN is poorly understood because its abundance in INPs has been confirmed only using advanced analytical techniques . The reduction of INP activity is believed to be caused by reducing the availability of IN active sites or changing the water activity of the core particle. Conversely, some coating materials are found to enhance IN activity. , For example, several studies reported the significant potential of organic aerosol to act as INPs, although not as efficiently as mineral dust particles. ,, The ubiquity of organic matter in a photochemically active environment affects the IN properties of aerosol by influencing their phase state (liquid to solid) and morphology. , The phase of organic aerosol affects the IN activity and the pathway to form ice. It is widely accepted that INPs contain insoluble and/or solid substrates that aid in the formation of ice crystals .…”
Section: Introductionmentioning
confidence: 99%
“…For example, surface-active per- and polyfluoroalkyl substances (PFAS) 293 likely affect ice nucleation of aerosol particles. 294 Interestingly, PFOA (perfluorooctanoic acid, a C8 carboxylic acid) can nucleate freezing at −16 °C, but PFOS (perfluorooctane sulfonic acid, a C8 sulfonic acid) is ineffective due to the bulky, disordered sulfonate head groups. 295 Furthermore, pH matters: neutral PFOA allows for ice nucleation, but anionic PFOA does not.…”
Section: Ice Nucleationmentioning
confidence: 99%